Personalities of Russian amateur botany, 3. Ivan M. Schvetzov and Theodor S. Nenukow, prominent experts in the flora of Nizhni Novgorod Region, and the taxonomic identity of plant species described by Nenukow - Sennikov, Alexander N.; Tikhomirov, Valery N.; Biryukova, Olga V.; Mininzon, Ilya L. (Memoranda Societatis pro Fauna et Flora Fennica, 2021)
Ivan Schvetzov collected many specimens of vascular plants, fungi, mosses and lichens mostly from the western part of Nizhni Novgorod Region of Russia, including the original collections of Cytisus ruthenicus var. zingeri Nenukow. Theodor Nenukow was a prominent amateur botanist from Nizhni Novgorod. He studied the flora of Nizhni Novgorod Region, weed and meadow flora of Central Russia and vascular plants of Estonia. He described a few infraspecific taxa and two species of vascular plants, Valeriana estonica Nenukow (synonymised here with V. officinalis subsp. tenuifolia (Vahl) Schübl. & G.Martens) and Odontites estonicus Nenukow (a synonym of O. vulgaris Moench), and the basionym for Cytisus zingeri (Nenukow) V.I.Krecz. (a glabrous variety of C. ruthenicus Fisch. ex Otto). The places of valid publication are clarified for C. ruthenicus var. zingeri and Persicaria linicola, and the lectotype is designated for C. ruthenicus var. zingeri.